The Relationship between Nutritional Status and Intellectual Intelligence In 4th-5th Grade Students at SD N 219 Inpres Pannambungan, Maros - Bulkis, Audya; Darmawansyih, Darmawansyih; Azis, Asrul Abdul; Suryaningsih, Rista (Indonesian Health Journal, 2024)
Nutritional status is a measure of the condition of a person's body, which can be seen from the food consumed and the use of substances in the body. The purpose of this study is to determine the relationship between nutritional status and intellectual intelligence in elementary school children in grades 4-5 at SDN 219 Inpres Pannambungan. In this study, the research design was observational, with a cross-sectional approach using total sampling. This study uses an intellectual intelligence test tool, namely the CFIT (Culture Fair Intelligence Test. Data analysis was carried out using the SPSS application by conducting univariate analysis related to respondent characteristics, independent variables, and dependent variables, then continued by conducting bivariate analysis, namely the Kolmogorov-Smirnov normality test and the Spearman correlation test. The results of this study showed that the correlation value (-2.72) with the probability value or error level (p=0.035) was smaller than the significant standard value (a=0.05). This study concludes that there is a significant relationship between nutritional status and the intellectual intelligence of children of SDN 219 Pannambungan Presidential Instruction Maros Regency.